2022
DOI: 10.1111/jcmm.17144
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 alleviates acute liver injury by inducing the SIRT1‐autophagy signalling pathway

Abstract: Liver injury can lead to different hepatic diseases, which are the mainly causes of high global mortality and morbidity. Autophagy and Sirtuin type 1 (SIRT1) have been shown protective effects in response to liver injury. Previous studies have showed that Fibroblast growth factor 21 (FGF21) could alleviate acute liver injury (ALI), but the mechanism remains unclear. Here, we verified the relationship among FGF21, autophagy and SIRT1 in carbon tetrachloride (CCl4)‐induced ALI. We established CCl4‐induced ALI mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…However, the incidence of acute liver injury (ALI) has gradually increased due to viral infections, improper medications, excessive intake and exposure of food additives, ethanol, ingestion of toxic foods, and radiation injury ( Bechmann et al, 2012 ; Chao et al, 2018 ; LoBianco et al, 2020 ; Xu et al, 2020 ). ALI refers to acute injury or necrosis of liver cells, abnormal liver function, and even liver failure in some patients ( Yang et al, 2022 ). Although liver cells have a strong ability to regenerate, ALI still threaten life if they are not treated in time.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of acute liver injury (ALI) has gradually increased due to viral infections, improper medications, excessive intake and exposure of food additives, ethanol, ingestion of toxic foods, and radiation injury ( Bechmann et al, 2012 ; Chao et al, 2018 ; LoBianco et al, 2020 ; Xu et al, 2020 ). ALI refers to acute injury or necrosis of liver cells, abnormal liver function, and even liver failure in some patients ( Yang et al, 2022 ). Although liver cells have a strong ability to regenerate, ALI still threaten life if they are not treated in time.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy inhibits TNF toxicity by blocking caspase 8 activation and mitochondrial death pathways in vivo, suggesting that autophagy is a potential therapeutic target in the treatment of TNF-α-induced liver injury [31]. Fibroblast growth factor 21 was recently found to attenuate CCl4-induced ALI through SIRT1speci c mediated autophagy-induced expression [32]. A previous study in our laboratory showed that enhanced autophagy accelerated the clearance of damaged mitochondria in drug-induced ALI in mice, thus providing a protective effect [14].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 induction by FGF21 enhances autophagy and reduces inflammation, which helps protect against CCl4-induced liver injury ( Yang et al, 2022b ). This suggests that the presence and activation of SIRT1 are crucial for mitigating liver injury and, by extension, preventing fibrosis.…”
Section: Survey Methodologymentioning
confidence: 99%